Exploring Interactions of People, Places and Information - McKenzie, Pam; Johnson, Catherine; Stevenson, Sarah (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2014)
Proceedings of the CAIS/ACSI 2011 conference.